The Effect of Movement Control Order During Covid19 Pandemic on Air Quality and Gas Emissions: A Review - Muhammad Azmi Maruf (Universitas Airlangga, 2020)
Introduction: Since the COVID-19 or novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) happened in December 2019, the number of cases has been rapidly increasing. To reducing the speed of infection, nations around the world have been doing movement control order (MCO) to their city for some time. The evidence shows that MCO can help many countries controlling the pandemic. The other effects of MCO is a change in air quality and gas emissions. The current study made for collecting evidence of how MCO affect air quality and gas emissions in several areas. This study aimed to explore if there are any positive and negative effects of movement control order (MCO) to air quality and gas emissions of areas that doing so. Discussion: During the movement control order (MCO) period, human outdoor activities have significantly reduced, affecting industrial operations reduction significantly, transportations, and other activities like constructions that leads to reduction of emissions. But there is increase of O3 and indoor pollution because of household activities increase. Many countries show that there are changes in air quality because of changes in human behaviour during movement control order. Conclusion: Current Studies concludes that the COVID-19 pandemic brings changes in air quality and emissions, as MCO, quarantine, and lighter traffic affect to better air quality outdoor, but, there is also increase of indoor pollutions. It is recommended that human should to maintain air quality by making reduction of unnecessary activities that make air quality worse.